Spiritual and Moral Education of Youth on the Basis of Kazakh Feature Films (Journal of Educational Sciences, 2020)
The article considers the issues of spiritual and moral education of young people on the basis of viewing Kazakh feature films. The purpose of the article is the analysis of modern cinematography to reveal the potential of spiritual and moral education of young people through feature films and the development of methodological recommendations. The authors conduct a comparative analysis of feature films of the Soviet period and the period of independent Kazakhstan in conventional diads (for example, “Kyz Zhibek” and “Tomiris”; “Kokserek” and “Shal”; other films).The table shows the main similarities and differences. The main similarities and differences of approaches to the ideas of films, the direction of meanings and accents of education are presented in tabular form. The authors emphasize the content of spiritual and moral values promoted in the films.Based on the views of scholars who have studied cinema and feature films, recommendations are given for the development of value qualities in young people. In practical part, the article presents the results of a survey of 146 students about their interests in the world of cinema art, preferences for genres of films, which allowed giving recommendations for the educational work of pedagogues. According to the survey, students watch Korean, Turkish, Russian, Indian, Chinese and American films and series. The authors emphasize that human values cannot be separated from the national worldview, folk ideology, customs, traditions, cinema, history, documentary, aesthetic views. Therefore, historical and ethnographic data should always be taken into account when con- sidering moral and human values.Key words: education, feature films, movie, moral and spiritual education, value, paradigm.